Immune reactivity after adenoviral‐mediated aquaporin‐1 cDNA transfer to human parotid glands. (8th February 2017) - Alevizos, I; Zheng, C; Cotrim, AP; Goldsmith, CM; McCullagh, L; Berkowitz, T; Strobl, SL; Malyguine, A; Kopp, WC; Chiorini, JA; Nikolov, NP; Neely, M; et al.
Abstract : Objectives: The purpose of this study was to examine the humoral and cellular immune reactivity to adenoviral vector (AdhAQP1) administration in the human parotid gland over the first 42 days of a clinical gene therapy trial. Methods: Of eleven treated subjects, five were considered as positive responders (Baum et al, 2012). Herein, we measured serum neutralizing antibody titers, circulating cytotoxic lymphocytes, and lymphocyte proliferation in peripheral blood mononuclear cells. Additionally, after adenoviral vector stimulation of lymphocyte proliferation, we quantified secreted cytokine levels. Results: Responders showed little to modest immune reactivity during the first 42 days following gene transfer. Additionally, baseline serum neutralizing antibody titers to serotype 5‐adenovirus generally were not predictive of a subject's response to parotid gland administration of AdhAQP1. Cytokine profiling from activated peripheral blood mononuclear cells could not distinguish responders and non‐responders. Conclusions: The data are the first to describe immune responses after adenoviral vector administration in a human parotid gland. Importantly, we found that modest (2–3 fold) changes in systemic cell‐mediated immune reactivity did not preclude positive subject responses to gene transfer. However, changes beyond that level likely impeded the efficacy of gene transfer.